Ensaios sobre redistribuição de renda na América Latina - Silva., Cleiton Roberto da Fonseca (2012)
This study aims to analyse the income redistribution in Latin American Countries from two essays. The first modeling redistributive preferences with special focus on the impact of mobility expectations on the demand for redistribution. The results suggest demand for self-interest and for considerations of justice based on inequality of opportunity. Furthermore, the results indicate the importance of past mobility and rejection the prospect of upward mobility (POUM) hypothesis of Benabou & Ok (2001). The second study evaluates the effects of income redistribution policies on esponsibility-sensitive" fairness levels in major Latin American countries. In doing so, the following items are analyzed: i) the fairness rule described in Bossert (1995), Konow (1996), and Cappelen & Tungodden (2007) and; ii) the redistribution mechanism (taxation policy) proposed by Ooghe & Peich (2010). The results indicate that taxation does not have a significant efect on Latin American fairness indicators. This behavior can be explained, among other factors, by the fiscal design used, which utilizes high rates associated with the effort variables and fails to equalize unequal opportunities. Additionally, as the redistribution does not equalize differential of opportunities and this is an important component of the redistributive preferences, there is a growing demand for redistribution that starts a specific vicious cycle in Latin American countries.